Atomically Dispersed Cu in Zeolitic Imidazolate Framework Nanoflake Array for Dendrite‐Free Zn Metal Anode. Issue 30 (30th June 2022) - Tao, Yuan; Zuo, Shou Wei; Xiao, Shu Hao; Sun, Peng Xiao; Li, Nian Wu; Chen, Jun Song; Zhang, Hua Bin; Yu, Le
Abstract: Aqueous Zn metal batteries (AZMBs) have been considered as a promising alternative to the existing Li‐ion batteries. Nevertheless, the large‐scale application of the AZMBs is restricted by the dendrite formation and side reactions within the Zn metal anodes (ZMAs) during cycling. Herein, an atomically dispersed Cu in leaf‐like Zn‐coordinated zeolitic imidazolate framework (ZIF‐L) nanoflakes on Ti mesh (CuZIF‐L@TM) as ZMA host is developed. The 3D conductive network formed by the interconnected ZIF‐L nanoflakes can reduce the local current density and homogenize the electric field distribution. Moreover, experimental data and theoretical calculations reveal the Cu single atoms within the ZIF‐L can serve as the zincophilic sites to facilitate the Zn deposition. As expected, the CuZIF‐L@TM host enables a homogeneous Zn deposition on the surface without dendrites. The resultant CuZIF‐L@TM/Zn electrode shows stable Zn plating/stripping over 1100 h at 1 mA cm −2 with a low voltage hysteresis of about 50 mV. As a proof of concept, a full cell based on the designed CuZIF‐L@TM/Zn anode shows a stable cycling performance over 1000 cycles. Abstract : A leaf‐like zeolitic imidazolate framework nanoflake array on Ti mesh decorated by Cu single atoms (CuZIF‐L@TM) is designed as host for stable Zn metal anode. Owing to porous structure and zincophilic Cu single atoms, the local current density is reduced to realize a uniform Zn deposition. The corresponding symmetric and full cells demonstrate good rate performance and long‐term cycling life.